Womanist Ethics as a Contribution to Bioethics. (26th April 2022) - Mack, April
Abstract: This essay argues that womanism, a social theory focused on the embodied lives of Black women, can be useful to bioethicists as they consider health care ethics during a pandemic—and beyond. A general social justice‐oriented ethical framework is helpful to begin a conversation on pandemic ethics, but it does not directly lead to the kind of on‐the‐margins‐of‐society framework that is necessary to increase health equity and justice. With particular concern for poor Black women, I discuss three main reasons that such an ethics framework needs to incorporate womanist ethics: the feminization of poverty, lack of access to high‐quality health care, and rape and other historical violence against Black women. I conclude by proposing that an understanding of womanism as a correlative to the Black Lives Matter clarion call can create an ethical narrative in bioethics that can exist beyond times of pandemic.